A five year CT surveillance of ciliated retroperitoneal foregut cyst resembling a cystic pancreatic lesion: A case report. Issue 21 (May 2018) - Chen, Hai-Yan; Wei, Shu-Mei; Chen, Jie-Yu; Zhu, Xiu-Liang; Yu, Ri-Sheng
Abstract: Introduction: Ciliated retroperitoneal foregut cysts are rare, and to obtain a preoperative definitive diagnosis of this condition is relatively difficult. In addition, the exact mechanism and formation of ciliated retroperitoneal foregut cysts remains unknown. Case presentation: Here, we report a case of a 47-year-old woman who presented with an unusual shaped cystic lesion associated with a patch of solid components between the pancreas and the left kidney, initially misdiagnosed as a cystic pancreatic lesion 5 years previously to presentation at our clinic. During the past years, reports relating to the surveillance of these lesions described that their shapes progressively change while its volumes remain invariably unchanged. We did not observe this phenomenon in any literatures to our knowledge. The patient was diagnosed with ciliated retroperitoneal foregut cyst with remote hemorrhage, after the laparoscopic surgery. Conclusions: Ciliated retroperitoneal foregut cysts have characteristic manifestations. From this case, we summarized that cysts in the retroperitoneum, associated with a changing shape of the lesion, highly suggest the diagnosis of foregut cysts, which are safe under long-term surveillance.